Peningkatan Kapasitas Organisasi melalui Penerapan Web Company Profile pada Komunitas UMKM Permata Hati Banyumas: Penelitian - Muhammad Hery Santoso; Rianti Yunita Kisworini; Lutvi Riyandari; Mury Andayani; Bayu Rizkya Pratama; Endang Setyawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Organizational capacity is an important foundation in maintaining the sustainability and competitiveness of the MSME community amidst the challenges of the digital era. This community service activity aims to increase the organizational capacity of the Permata Hati Banjoemas Foundation through training and socialization of the implementation of a web company profile equipped with e-commerce features. The activity was held on Monday, July 21, 2025, at the Lumbung Pari Tengah Sawah Restaurant, Banyumas, and was attended by 20 participants consisting of foundation administrators and representatives of the fostered MSME community. The material was delivered by a team of lecturers from STMIK Widya Utama and STIKOM Yos Sudarso alternately, with a practical approach in the form of presentations, website demonstrations, and interactive discussion sessions. Participants were equipped with an understanding of the importance of an organization's digital existence as well as basic skills in managing web-based information systems. The results of the activity showed a significant increase in participants' understanding and skills in utilizing information technology to support transparency, promotion, and organizational performance.